Mandibular meningioma—a rare case report of a second extracranial meningioma and a systematic literature review - Dionísio, Sílvia Rodrigues; Ventura, Eduardo Simões; Ferreira, Ângela Tavares; Gonçalves, Joana Bolinha; Saleiro, Rute Vaz; Marques, Hugo Martins; Dias, Alfredo Figueiredo (Journal of surgical case reports, 2020)
Abstract Meningiomas are benign tumours common in the central nervous system. Primary extracranial meningiomas in the jaws are extremely rare. We performed a systematic review of all the primary extracranial meningioma arising in the jawbones reported in the English-language literature including indexed and non-indexed journals and we report a unique case in our hospital of a man with two primary extracranial meningiomas, the first frontal intradiploic and 16 years later, a second located in the mandible. We found 14 cases with primary jaws meningioma and we report another one. A mandibular predominance was observed with only four cases in the maxilla. Most of them occurred in women, with a mean age of 35.9 years. It is the first published case of a patient with two primary extracranial meningiomas one of them in the mandible, which the gender, age and laterality of the lesion are less frequent.